Analisis Historiografi Terhadap Pemikiran Azyumardi Azra Dalam Jaringan Ulama - Hakim, Lukmanul; Arsa, Dedi; Meria, Aziza; Sandora, Lisna (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2020)
Azyumardi Azra's work, The Networks of Malay-Indonesian and Middle Eastern ‘Ulama in the Seventeenth and Eighteenth Century: The Root of Islamic Reformism, is important, as it presents the transmission of ideas and Islamic teachings via the network of ‘Ulama. Another important aspect of this book is its use of primary sources (ancient manuscripts and the books written in Arabic and English). Azra’s book, in my opinion, is the first book which utilizes such an extensive array of Arabic sources to study the history of Islamic Reformism in the Malay Archipelago. The purpose of this article is to describe and analyze the methods, the theories, the historical school of thought, and the approaches used by Azra in the process of writing this book. The article employs historical research method and historiographical approach. The result is crystal-clear, Azra wrote the book using the scientific historical research method with its four steps of research: heuristic, source-criticism, interpretation, and historiography. The main keywords within this book are transmission and network. Azra was also inclined toward ‘the new history’ school of thought. Finally, we can mention for sure that Azra approached the research problem through the local and global perspectives simultaneously. His work is undoubtedly a major contribution into the body of literature and has inspired many enthusiasts and the scholars of Southeast Asian studies, as well as the scholars of the seventeenth and the eighteenth-century Muslim World. Keywords: Azyumardi Azra, Indonesian Islamic Historiography, Ulama Network Karya Azyumardi Azra dengan judul Jaringan Ulama Timur Tengah dan Kepulauan Nusantara Abad XVII & XVIII Akar Pembaruan Islam Indonesia ini sangat penting, karena telah menyajikan aspek intelektual yang mengetengahkan bentuk gagasan dan ajaran yang ditransmisikan melalui jaringan ulama. Yang lebih penting lagi adalah sumber yang digunakan Azra dalam bukunya tersebut adalah sumber-sumber primer dalam bentuk manuskrip-manuskrip dan buku-buku cetakan berbahasa Arab dan Inggris. Tampaknya inilah buku pertama yang menggunakan sumber-sumber Arab secara ekstensif dalam pengkajian yang berkenaan dengan sejarah pembaruan pemikiran Islam di Nusantara. Tujuan tulisan ini adalah mendeskripsikan dan menganalisis metode, teori, aliran pemikiran sejarah dan pendekatan yang digunakan Azra dalam penulisan buku Jaringan Ulama. Metode yang digunakan adalah metode historis dengan pendekatan historiografi. Tulisan ini berhasil mengetengahkan metode yang digunakan Azra yaitu metode sejarah ilmiah dengan empat tahapan, yaitu-heuristik, kritik sumber, interpretasi, dan historiografi. Teori yang digunakan transmission dan network. Azra lebih cenderung kepada aliran pemikiran sejarah New History. Sedangkan pendekatan yang digunakannya adalah Azra melihat perjalanan historis Islam di Nusantara harus dilihat dari perspektif global dan lokal sekaligus. Karya Azra ini memberikan konstribusi besar kepada literatur dan menjadi inspirasi bagi peminat dan penulis kajian Asia Tenggara serta dunia muslim pada abad ke-17 dan ke-18. Kata Kunci: Azyumardi Azra, Historiografi Islam Indonesia, Jaringan Ulama